The concept of acclimatization - Monge M., Carlso (1955)
What characterizes life in Central Highlands America is the geographical environment dfe altitude that gives the body special features brought out by the work of Peruvian researchers. It has been said that Peru offers all climates of the world. Actually what this peculiar climate are two types to a territory located in the tropics, inhabited up to 15,000 feet altitude (5,000 mts.). So over the snowy ridges, the climate is tropical glacial type. It seems to be speaking a paradox. On the high plains is tropical and cold type; in the lower plateau is temperate, and, finally, it is only warm in the Jungle, the only type comprises acclimated to that in other areas of the earth.